Power production mix transition: Case of the Czech Republic and Germany - Jakub Zezula (World Economy and Policy (WEP), 2022)
Countries of the EU have to transform their power production mix in order to meet the targets of the greenhouse gas emissions of the Union. The goal of the article is to investigate two approaches to the transition of the power production mix. Germany and the Czech Republic represent an example of states with a different position in this process as well as a different approach to it. While Germany has a clear timetable for this transition and relies on renewable sources (dominantly wind), the Czech Republic sets a general target represented by a year of the planned closure of the coal utilities (2038) and will probably mostly rely on nuclear power plants. Due to the high share of unstable wind and solar sources, the German market experiences high volatility of power prices and the export of electricity. The Czech market is affected by the market conditions in Germany; however, the country is self-sufficient to cover its power demand at the moment. Nevertheless, this fact can be endangered by decreasing the availability of the conventional power sources (in combination with the absence of a clear strategy of their substitution) and potential increase of power consumption.
Keywords: M00; M21; O13; 330; energy transition; power production; energiewende; power markets; fit for 55; european green deal